Sex-specific bacterial microbiome variation in octopus vulgaris skin - Rodríguez-Barreto, Deiene; Sanz-González, Juan Carlos; Martín, M. Virginia; Arrieta, Jesús M.; Almansa, Eduardo (Frontiers in Microbiology, 2024)
Growing knowledge of the host-microbiota of vertebrates has shown the prevalence of sexspecific differences in the microbiome. However, there are virtually no studies assessing sexassociated variation in the microbiome of cephalopods. Here we assess sex-specific variation in the common octopus (Octopus vulgaris) skin microbiome using amplicon sequencing targeting the V4 hypervariable region of prokaryote 16S rRNA genes. Skin and mantle-associated mucus was collected from wild adult individuals of common Octopus (Octopus vulgaris) (9 males and 7 females of similar size). There were no significant differences in the alpha diversity of microbial communities associated with skin or mantle mucosa between sexes. However, our results clearly indicate that adult octopus males and females have a distinct microbial community composition in both skin and mantle associated mucus communities, with female microbiome being dominated by Firmicutes (48.1%), while that of males contained a majority of Proteobacteria (60.5%), with Firmicutes representing only 3.30%, not finding significant differentiation in the microbial communities between the tissues explored. The dominance of different taxa in the skin of O. vulgaris females and males (e.g. Mycoplasmatales and Lactococcus in females and Rhizobiales and Rhodobacteriales in males) suggests a sex-specific symbiosis in which those microbes benefit from easy access to distinct substrates present in female and male skin, respectively. Given the lack of differences in size between specimens of both sexes in this study, we hypothesize differences in hormone profile, as well as behavioural or ecological differences between sexes in the wild, as the main drivers of microbiome differentiation between sexes.Most knowledge of cephalopod microbiota is limited to the digestive tract and the reproductive system. However, cephalopod skin is an organ with a plethora of functions. This is a first attempt to characterize cephalopod skin microbiota and determine sex influence on it.